Shelf sediment transport during hurricanes Katrina and Rita - Xu, Kehui; Mickey, Rangley C.; Chen, Qin; Harris, Courtney K.; Hetland, Robert D.; Hu, Kelin; Wang, Jiaze (Computers & geosciences, 2016)
Hurricanes can greatly modify the sedimentary record, but our coastal scientific community has rather limited capability to predict hurricane-induced sediment deposition. A three-dimensional sediment transport model was developed in the Regional Ocean Modeling System (ROMS) to study seabed erosion and deposition on the Louisiana shelf in response to Hurricanes Katrina and Rita in the year 2005. Sensitivity tests were performed on both erosional and depositional processes for a wide range of erosional rates and settling velocities, and uncertainty analysis was done on critical shear stresses using the polynomial chaos approximation method. A total of 22 model runs were performed in sensitivity and uncertainty tests. Estimated maximum erosional depths were sensitive to the inputs, but horizontal erosional patterns seemed to be controlled mainly by hurricane tracks, wave–current combined shear stresses, seabed grain sizes, and shelf bathymetry. During the passage of two hurricanes, local resuspension and deposition dominated the sediment transport mechanisms. Hurricane Katrina followed a shelf-perpendicular track before making landfall and its energy dissipated rapidly within about 48h along the eastern Louisiana coast. In contrast, Hurricane Rita followed a more shelf-oblique track and disturbed the seabed extensively during its 84-h passage from the Alabama–Mississippi border to the Louisiana–Texas border. Conditions to either side of Hurricane Rita’s storm track differed substantially, with the region to the east having stronger winds, taller waves and thus deeper erosions. This study indicated that major hurricanes can disturb the shelf at centimeter to meter levels. Each of these two hurricanes suspended seabed sediment mass that far exceeded the annual sediment inputs from the Mississippi and Atchafalaya Rivers, but the net transport from shelves to estuaries is yet to be determined. Future studies should focus on the modeling of sediment exchange between estuaries and shelves and the field measurement of erosional rates and settling velocities. •Erosional depths were sensitive to both erosional rates and settling velocities.•Local resuspension and deposition dominated the sediment transport mechanisms.•East of hurricane tracks has stronger winds, taller waves and deeper erosions.•Hurricanes suspended seabed sediment mass far exceeding the annual river inputs.